2017
DOI: 10.1097/md.0000000000006545
|View full text |Cite
|
Sign up to set email alerts
|

The comparative preemptive analgesic efficacy of addition of vitamin B complex to gabapentin versus gabapentin alone in women undergoing cesarean section under spinal anesthesia

Abstract: Background:Development of new multimodal analgesic regimens have led to substantial improvement in postoperative pain relief. We designed this study to compare the effect of combined vitamin B complex—gabapentin versus gabapentin alone on postoperative pain in women undergoing cesarean section under spinal anesthesia.Methods:One hundred twenty-eight women who underwent cesarean section under spinal anesthesia were randomized to receive orally 300 mg gabapentin (group G) or 300 mg of gabapentin plus 2 vitamin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Un probable motivo por el cual no encontraron una superioridad analgésica significativa para el grupo de diclofenaco más vitaminas B (como ha sido reportado en otras investigaciones), es que el número de administraciones y la dosis de vitamina B 12 fueron menores a las administradas en otras investigaciones. Reportaron también que el requerimiento de diclofenaco intravenoso postoperatorio fue significativamente menor en el grupo pretratado con diclofenaco más vitaminas B, lo cual sugiere que la administración preoperatoria de vitaminas B 1 , B 6 y B 12 puede reducir el consumo postoperatorio de AINE [15][16][17][18][19] .…”
Section: Discussionunclassified
“…Un probable motivo por el cual no encontraron una superioridad analgésica significativa para el grupo de diclofenaco más vitaminas B (como ha sido reportado en otras investigaciones), es que el número de administraciones y la dosis de vitamina B 12 fueron menores a las administradas en otras investigaciones. Reportaron también que el requerimiento de diclofenaco intravenoso postoperatorio fue significativamente menor en el grupo pretratado con diclofenaco más vitaminas B, lo cual sugiere que la administración preoperatoria de vitaminas B 1 , B 6 y B 12 puede reducir el consumo postoperatorio de AINE [15][16][17][18][19] .…”
Section: Discussionunclassified
“…In the two latter studies, basic analgesia consisted of diclofenac [21,22]. In a study conducted on patients who did not receive any basic analgesia, adding vitamin B complex to gabapentin reduced pain scores and opioid consumption compared with the use of gabapentin alone [23]. A systematic review reported a clinically significant reduction in 24-h pain scores with pre-operative gabapentin.…”
Section: Systemic Non-opioid and Opioid Analgesicsmentioning
confidence: 99%
“…Four randomised controlled trials [20][21][22][23] and a metaanalysis [24] evaluated pre-operative gabapentinoids for analgesia after caesarean section. No significant benefits were reported with gabapentin when added to a multimodal analgesia regimen [20].…”
Section: Systemic Non-opioid and Opioid Analgesicsmentioning
confidence: 99%
“…Multimodal analgesia is established in the management of pain after cesarean section (CS), and different regimens are being tested. [ 1 ] However, the most popular strategies include intrathecal opioids, among which morphine, a hydrophilic opioid, is recognized as a gold standard. [ 2 ] It has been shown that morphine can provide postoperative analgesia for up to 24 hours, [ 3 ] and a dose of up to 100 μg is relatively safe in patients undergoing CS.…”
Section: Introductionmentioning
confidence: 99%